2012
DOI: 10.1111/jvh.12042
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic APOBEC3 modulates chronic hepatitis B in Moroccan population

Abstract: The cytidine deaminase apolipoprotein B mRNA editing catalytic subunit-3 (APOBEC3) induces G-to-A hypermutation in hepatitis B virus (HBV) genomes and operates as part of the innate antiviral immune system. We investigated the associations between the presence of APOBEC3 variants and HBV carriage in a case-control study in the Moroccan population. A polymorphic deletion affecting the APOBEC3B gene and the H186R variant of APOBEC3G were genotyped in 179 HBV chronic carriers and 216 healthy control subjects. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
2
23
0
1
Order By: Relevance
“…In a subsequent study, it was shown that the overexpression of A3A induced hypermutation in the HBV genome, although the levels of hypermutants were less than those introduced by A3G (Abe et al, 2009). A third study examined the correlation between deletion of the A3B gene and chronic HBV infections (Ezzikouri et al, 2013). These investigators observed that patients with the A3B-deleted genotype had lower virus burdens than those patients without the A3B-deletion phenotype (Ezzikouri et al, 2013).…”
Section: A3a Restriction Of Dna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, it was shown that the overexpression of A3A induced hypermutation in the HBV genome, although the levels of hypermutants were less than those introduced by A3G (Abe et al, 2009). A third study examined the correlation between deletion of the A3B gene and chronic HBV infections (Ezzikouri et al, 2013). These investigators observed that patients with the A3B-deleted genotype had lower virus burdens than those patients without the A3B-deletion phenotype (Ezzikouri et al, 2013).…”
Section: A3a Restriction Of Dna Virusesmentioning
confidence: 99%
“…A third study examined the correlation between deletion of the A3B gene and chronic HBV infections (Ezzikouri et al, 2013). These investigators observed that patients with the A3B-deleted genotype had lower virus burdens than those patients without the A3B-deletion phenotype (Ezzikouri et al, 2013). A3A has also been shown to inhibit the replication of papillomaviruses (Ahasan et al, 2015;Warren et al, 2015).…”
Section: A3a Restriction Of Dna Virusesmentioning
confidence: 99%
“…A previous study investigated the relationship between rs8177832 and CHB in 179 HBV chronic carriers and 216 healthy control subjects in a Moroccan population[31]. The results showed that the G genotype tended to be associated with an increased risk of developing CHB ( P = 0.254).…”
Section: Discussionmentioning
confidence: 98%
“…Due to the A3B ability of restricting HBV, it has been suggested that this gene deletion can result in reduced viral clearance, culminating with persistent infection [97]. In other studies, the homozygosity status for the deletion was associated with mild liver fibrosis, but not with a chronic carrier status [95], and with faster progression of liver disease [98]. Homozygous individuals for this deletion have also been reported with an increased risk for HIV acquisition, for a higher viral set point and for progression to AIDS [94], yet no effect was found on susceptibility to HIV infection and AIDS in Japanese or Indian populations [96].…”
Section: Polymorphisms In Apobec3 Genes and Susceptibility To Viramentioning
confidence: 99%